Economic growth or redistribution? - Jürgen Westphalen (Intereconomics, 1976)
Economic and development policies in Latin America, as in all other developing countries, are supposed to tackle the problem how to increase total income and, at the same time, how to reduce the present inequalities in the distribution of income. The opinions on the question, which of these tasks deserves priority, differ widely.
Keywords: 330; Latin America